Frequency Domain Analysis of Continuous Systems with Viscous Generalized Damping - S. Sorrentino; A. Fasana; S. Marchesiello (Shock and Vibration)
This paper deals with the effects of generalized damping distributions on vibrating linear systems. The attention is focused on continuous linear systems with distributed and possibly non-proportional viscous damping, which are studied in terms of modal analysis, defining and discussing the orthogonality properties of their eigenfunctions.